(untitled) (World Bulletin of Management and Law, 2023)
In this research work, which was carried out in order to implement the tasks for the development of digital education in the order of the President of Uzbekistan on the approval of the strategy "DIGITAL UZBEKISTAN - 2030" and measures for its effective implementation, education system, including the development of digital competence by using cloud technologies and using them as a tool in the training of future teachers is of great importance